Cytotoxicity and mechanical properties of biphasic calcium phosphate scaffold from Tegilarca granosa due to its composition - Prananingrum, Widyasri; Caroline, Grace; Rizal, Mohammad Basroni; Prabowo, Puguh Bayu; Pratama, Afif Fahwi; Resaldi, Muhammad Firdan; Annisa, Nindya Yuanita; Fadhilah, Yusti; Sari, Rima Parwati (Odonto : Dental Journal, 2023)
Background: Biphasic calcium phosphate (BCP) is graft material contained HA and TCP. Tegilarca granosa shell is a natural source that may converted into BCP. This study aims to determine the composition and cytotoxicity of BCP synthesized from Tegilarca granosa shell used various hydrothermal hours and to evaluate the mechanical properties of BCP scaffold. Methods: Tegilarca granosa shell was converted into BCP using hydrothermal method at 200ËšC for 6h (Group 1); 9h (Group 2); and 12h (Group 3). The composition was determined by XRD and the cell viability were evaluated using MTT Assays. Each group was added with 20% gelatin ratio 50:50 (w/v) and freeze-dried to form scaffold. Scaffolds (Ã˜6mm x 4mm) were prepared for diametral tensile strength (DTS) test (n=6) and scaffolds (Ã˜7mm x 11mm) were used for compressive strength (CS) test (n=6). All data were analyzed using Kruskall-Wallis followed by Mann-Whitney test. Results: The composition of BCP (HA/ TCP) at Group 1, Group 2, and Group 3 were 81.80%/14,10%; 87%/6%; and 72%/21%. The cell viabilities were good for all groups. The DTS and CS test showed there was a significant difference between Group 1 and Group 3 scaffold, meanwhile there was no significant differences between Group 2 and Group 3 scaffold. Group 3 scaffold showed the highest DTS and CS, 6.921 MPa and 1,233 MPa. Conclusion: The BCP composition were depent on hydrothermal hours. Although all scaffold groups were non-toxic, but BCP scaffold synthesized from Tegilarca granosa shell using hydrothermal for 12 hours showed the highest mechanical properties.